Structural Variations of Metal Oxide‐Based Electrocatalysts for Oxygen Evolution Reaction. Issue 12 (27th October 2021) - Gao, Ruiqin; Deng, Meng; Yan, Qing; Fang, Zhenxing; Li, Lichun; Shen, Haoyu; Chen, Zhengfei
Abstract: Electrocatalytic oxygen evolution reaction (OER), an important electrode reaction in electrocatalytic and photoelectrochemical cells for a carbon‐free energy cycle, has attracted considerable attention in the last few years. Metal oxides have been considered as good candidates for electrocatalytic OER because they can be easily synthesized and are relatively stable during the OER process. However, inevitable structural variations still occur to them due to the complex reaction steps and harsh working conditions of OER, thus impending the further insight into the catalytic mechanism and rational design of highly efficient electrocatalysts. The aim of this review is to disclose the current research progress toward the structural variations of metal oxide‐based OER electrocatalysts. The origin of structural variations of metal oxides is discussed. Based on some typical oxides performing OER activity, the external and internal factors that influence the structural stability are summarized and then some general approaches to regulate the structural variation process are provided. Some operando methods are also concluded to monitor the structural variation processes and to identify the final active structure. Additionally, the unresolved problems and challenges are presented in an attempt to get further insight into the mechanism of structural variations and establish a rational structure–catalysis relationship. Abstract : Metal oxides are widely considered as candidates for the oxygen evolution reaction (OER). Structural variations, i.e., phase transition, dissolution, and valence state variation, are common phenomena for most of them. During OER, both the external and internal factors have direct correlations with the structural stability of them. Their structural stability can be effectively regulated by some chemical strategies.